A Theory of the Effect of Corporate Income Tax on the Optimal - Mantell, Edmund H (Advances in Social Sciences Research Journal, 2019)
Most professional and public discussions of the reduction of the corporate income tax rate in the United States (enacted in year 2017) focus on its income-distributive effects. This article addresses the question how, if at all, the change in the tax rate can be expected to affect a firm’s decision with respect to its optimal output and consequent deployment of factor inputs. The theory developed in this article assumes the firm faces an uncertain demand function embodying an additive random variable. The article derives three propositions relating the change in the tax rate and the firm’s output to the firm’s attitude towards risk.